Strategi Madrasah Tsanawiyah Sabilil Muttaqin Badas Kediri dalam Mewujudkan Visi dan Misi Madrasah - Fuadiy, Moch. Rizal; Rizal, Ahmad Fahrur (DIMAR: Jurnal Pendidikan Islam, 2023)
This research is a descriptive qualitative study. This research was conducted at Sabilil Muttaqin Badas Islamic Junior High School (Madrasah Tsanawiyah) in Kediri Regency from May to September 2022. The purpose of this research is to determine the strategies used by MTs Sabilil Muttaqin Badas-Kediri school in realizing the school's vision and mission, as well as the supporting and inhibiting factors. The data collection methods used are interviews, observations, and documentation. To ensure the validity of the data, the observation period was extended and triangulation was employed. The findings of this research include several discoveries. First, the strategies implemented by the school include: using the appropriate curriculum, namely K13, prioritizing the admission of female students, improving the quality and quantity of teachers, implementing Quranic values, mandatory memorization of the Quran for all students, placing teachers according to their expertise, setting an example for all teachers, selecting competent Quran memorization teachers, and paying attention to students' memorization progress. Second, there are supporting and inhibiting factors in realizing the school's vision. Supporting factors include the presence of young teachers, teachers' expertise in religious studies, adequate dormitory facilities, and comprehensive learning resources. On the other hand, inhibiting factors include differences in students' abilities, lack of student participation in the dormitory program, challenges in program implementation, insufficient library facilities, and a shortage of dormitory administrators. Third, the achievement of Quran memorization results is still below the current target.